2011 IEEE Nanotechnology Materials and Devices Conference 2011
DOI: 10.1109/nmdc.2011.6155293
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of two different CNT/polymer composites: CNT/PMMA and CNT/PmPV

Abstract: Carbon nanotube ( CNT) in polymeric matrix is investigating due to improvement of the structural, mechanical, thermal and electronic properties of resulting CNT/polymer composite. This improvement depends on: properties, features and volume fractions ofCNTs and polymer. In this paper, there are three main parts for using an analysis on a finite element model simulation ( FEM): carbon nanotube, surrounding polymer and interaction region between carbon nanotube and its surrounding polymer that van der Waals forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The origin of the enhancement in the ferroelectric properties of PVDF is still under investigation. Several reports demonstrated the templating effect of CNT in semicrystalline polymer/CNT blend systems. CNTs can act as templates and direct the crystal growth of semicrystalline polymers such as poly­(ethylene oxide), polypropylene, poly­(ε-caprolactone), and polyethylene. It is generally appreciated from previous investigations of the influence of CNTs on the crystalline microstructure of semicrystalline polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the enhancement in the ferroelectric properties of PVDF is still under investigation. Several reports demonstrated the templating effect of CNT in semicrystalline polymer/CNT blend systems. CNTs can act as templates and direct the crystal growth of semicrystalline polymers such as poly­(ethylene oxide), polypropylene, poly­(ε-caprolactone), and polyethylene. It is generally appreciated from previous investigations of the influence of CNTs on the crystalline microstructure of semicrystalline polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] From the studies, it is understood that the material properties of the CNT-reinforced polymer mainly depends on the structure of CNT, type of polymer, dispersion of CNT in matrix, fabrication process, and the method of analysis. [13][14][15][16] From the studies, it is understood that the material properties of the CNT-reinforced polymer mainly depends on the structure of CNT, type of polymer, dispersion of CNT in matrix, fabrication process, and the method of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many investigations are reported on the theoretical behavior of CNTRC flat/shell panel including the experimental validation. [13][14][15][16] From the studies, it is understood that the material properties of the CNT-reinforced polymer mainly depends on the structure of CNT, type of polymer, dispersion of CNT in matrix, fabrication process, and the method of analysis. Fidelus et al [17] reported the experimental data of the thermal and the mechanical properties of CNT/polymer composite using two types of polymer, as well as two CNT configurations based on the number of walls namely, singlewalled carbon nanotube (SWCNT) and multi-walled carbon nanotube (MWCNT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation